Expression of Bruton´s tyrosine kinase in different type of brain lesions of multiple sclerosis patients and during experimental demyelination - Elkjaer, Maria L.; Waede, Mie R.; Kingo, Christina; Damsbo, Karina; Illes, Zsolt (Frontiers in Immunology, 2023)
Background: Inhibition of Bruton's tyrosine kinase (BTK) is an emerging multiple sclerosis (MS) therapy. BTK inhibitors (BTKi) cross the blood-brain barrier and modulate B cells and microglia, major cellular players in active and chronic active lesions.Objective: To assess potential lesional and cellular targets of BTKi, we examined BTK expression in different type of MS white matter (WM) lesions, in unmanipulated CNS resident cells, and in a degenerative MS model associated with microglia activation in vivo.We examined BTK expression by next-generation RNA-sequencing in postmortem 25 control WM, 19 NAWM, 6 remyelinating, 18 active, 13 inactive and 17 chronic active lesions. Presence of B cells and microglia were examined by immunohistochemistry. CNS resident cells were isolated from the mouse brain by magnetic sorting. BTK expression was examined by quantitative PCR in isolated cells and dissected corpus callosum from mice treated with cuprizone (CPZ).Results: BTK expression was significantly increased in active and chronic active lesions with upregulated complement receptors and Fc receptors. Active lesions contained high number of perivascular B cells, microglia, and macrophages. Chronic active lesions were characterized by microglia/macrophages in the rim. Microglia expressed BTK at high level (120-fold) in contrast to This is a provisional file, not the final typeset article other CNS cell types (2-4-fold). BTK expression was increasing during CPZ treatment reaching significance after stopping CPZ.Considering BTK expression in MS lesions and resident cells, BTKi may exert effect on B cells, microglia/macrophages in active lesions, and limit microglia activation in chronic active lesions, where tissue damage propagates.